Optimization of Digital Marketing Strategies to Increase Revenue from The Tourism Sector in Kota Pari Village - Ritonga, Husni Muharram; Daulay, Muhammad Toyib; Erwansyah, Erwansyah; Mukti, Jihan Tri (Universitas Negeri Medan, 2023)
Kota Pari Village, PantaiCermin District, SerdangBedagai Regency, was the focus of this research because its residents saw a need to promote its tourist attractions online. The term